Peningkatan Kemampuan Numerasi Menggunakan Model Problem Based Learning Berbantuan Media KONTUAN - Aditya Haryanto; Diana Ermawati; Mohammad Syaffruddin Kuryanto (Mathematics Education Study Program, 2025)
This study aims to prove the Problem Based Learning model assisted by KONTUAN (Dakon Card Multiplication) to improve the numeracy skills of students in grade 3 Kayuapu Elementary School. This study used a quantitative experimental method with a one-group pretest-posttest design. Saturated sampling technique was used, with a population of 16 grade 3 students, consisting of 7 boys and 9 girls, where the entire population was used as the research sample. The measurement of the research results was carried out through the N-Gain test, which serves to determine the extent of the improvement of students' numeracy skills after the application of the Problem Based Learning model assisted by KONTUAN media. The N-Gain test results show an average value of 0.6273 which is included in the moderate category, this is appropriate because it is in the range of 0.30 ≤ 0.70. This research shows that the application of Problem Based Learning model with KONTUAN media is very meaningful in improving numeracy skills on multiplication material. In addition, the results showed that the use of models and media is an interesting and effective learning strategy in improving student activeness and numeracy skills. Thus, the Problem Based Learning model assisted by KONTUAN media can be one of the recommendations for learning methods for materials related to calculation .